Design and fabrication of portable sink / Amir Faris Helmi - Helmi, Amir Faris (2024)
A portable sink is a project that work basically just the same as traditional sinks because it completely supplied with water supplies. The difference between traditional and this portable sink are a portable sink is not connected with plumbing system, so water does not flow from the source and into the pipes. Most of the food stalls are facing difficulties due to lack of sink in their stall. Mostly, owners will bring pail or water container from their home to the stall to be use as their sink. Other than that, traditional sink needs plumbing system to supply water that would be hard for food truck vendors to install at their stall. Besides, some improvement features are added in this project to make an easier for them to use sink at their stall and this project also can bring them easily with folding method that can reduce space used to store the sink. Additionally, this project also used no plumbing system for the sink and the anchor for the sink used material from stainless steel that difficult to rust if it used at outdoor event. The objective of this project is to provide clean and safe running water for handwashing stations wherever it may be needed. In conclusion, hope this project will help all of food stalls to solve their problems in having clean water